Etika Komunikasi Perspektif Al-Qur’an Dalam Menanggulangi Ujaran Kebencian Di Media Sosial - Mawaliya Mawaliya; Kusnadi Kusnadi; Aristhopan Firdaus (Journal of Literature Review, 2025)
The rapid growth of social media in Indonesia has attracted widespread public interest across various segments of society. However, its use remains largely dominated by personal and entertainment-oriented activities, whereas digital technological advancements should be utilized in a more productive manner. At the same time, communication practices on Indonesian social media platforms face serious challenges in the form of moral and ethical decline, one of which is the increasing prevalence of hate speech. This study employs a qualitative method with a library research approach and applies the maudhu‘i method of Qur’anic interpretation to inventory verses related to the term qaulan in the Qur’an. The research aims to examine the concept of communication ethics in the Qur’an, relate it to the phenomenon of hate speech on social media, analyze the impacts of such communication practices, and propose solutions for addressing hate speech through the understanding and application of qaulan-based communication ethics. The findings reveal that the concept of qaulan in Islamic communication ethics encompasses qaulan sadidan (truthful speech), qaulan balighan (effective and impactful speech), qaulan ma‘rufan (appropriate and kind speech), qaulan kariman (honorable speech), qaulan layyinan (gentle speech), and qaulan maysuran (clear and easily understood speech). These principles emphasize that communication should be conducted politely, honestly, gently, and with respect for others. In the context of social media, communication ethics based on the concept of qaulan are highly relevant for addressing challenges such as hate speech, which has the potential to trigger conflict and undermine national unity.